The distribution of average and marginal effective tax rates in European Union member states - Herwig Immervoll (University of Essex, Institute for Social and Economic Research (ISER), 2002)
Macro-based summary indicators of effective tax burdens cannot provide information on the level or distribution of the marginal effective tax rates thought to influence household behaviour. They also do not capture differences in effective tax rates facing different subgroups of the population. I use EUROMOD, an EU-wide tax-benefit microsimulation model, to compute distributions of average and marginal effective tax rates across the household population in fourteen European Union Member States. Using different definitions of `net taxes', the tax base and the unit of analysis I present a range of measures showing the contribution of the tax-benefit system to household incomes; average effective tax rates applicable to income from labour; and marginal effective tax rates faced by working men and women. In a second step, these measures are broken down to separately analyse the influence of each type of tax-benefit instrument. The results show that measures of effective tax rates vary considerably depending on incomes, labour market situations and family circumstances. Using single averages or macro-based indicators will therefore provide an inappropriate picture of tax burdens faced by large parts of the population.
Keywords: H22; D31; C81; 330; Effective Tax Rates; European Union; Microsimulation; Steuertarif; Grenzsteuersatz; Simulation; EU-Staaten